2002
DOI: 10.1128/jvi.76.12.6235-6243.2002
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of the Sites of Cowpea Mosaic Virus RNA Replication into a Cytopathic Structure

Abstract: Cowpea mosaic virus (CPMV) replication induces an extensive proliferation of endoplasmic reticulum (ER) membranes, leading to the formation of small membranous vesicles where viral RNA replication takes place. Using fluorescent in situ hybridization, we found that early in the infection of cowpea protoplasts, CPMV plus-strand RNA accumulates at numerous distinct subcellular sites distributed randomly throughout the cytoplasm which rapidly coalesce into a large body located in the center of the cell, often near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Replication-associated proteins were also shown to colocalize at this site (21,42). Infection of ER-GFP plant cells by other picornavirus-like viruses (including CPMV and TEV) is also characterized by the induction of GFP aggregates similar to the ones described here, and the replication proteins of these viruses colocalize with the modified ER membranes (6,7,47). Several viral proteins expressed outside the context of the virus genome have been shown to localize to intracellular membranes and to induce the alteration of the morphology of these membranes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Replication-associated proteins were also shown to colocalize at this site (21,42). Infection of ER-GFP plant cells by other picornavirus-like viruses (including CPMV and TEV) is also characterized by the induction of GFP aggregates similar to the ones described here, and the replication proteins of these viruses colocalize with the modified ER membranes (6,7,47). Several viral proteins expressed outside the context of the virus genome have been shown to localize to intracellular membranes and to induce the alteration of the morphology of these membranes.…”
Section: Discussionmentioning
confidence: 74%
“…Many positive-strand RNA viruses induce extensive proliferation and modification of intracellular membranes in their hosts, which often results in the accumulation of numerous membranous vesicles. Doublestranded RNA (dsRNA) replication intermediates and viral replication factors are associated with the membranous vesicles, which are thought to be the site of the replication (6,7,18,25,48,49,52). The requirement for intact membranes for successful virus replication has also been demonstrated using cell-free replication systems (2,35,59).…”
mentioning
confidence: 99%
“…Exactly how RNA2 recruits RNA1-encoded proteins to replicate itself is not well understood for BPMV or comoviruses in general. Earlier investigations using CPMV, another comovirus, showed that mutations disrupting the coding region of the N-terminally located P58 open reading frame (ORF) abolished RNA2 accumulation in protoplast cells, although it was not further examined whether the P58 protein itself or its coding RNA played a more critical role or how this genome region facilitated RNA2 accumulation (11,20,21). It was also found that RNA2 of GFLV, a virus of the genus Nepovirus of the Secoviridae family, encodes a 5=-proximal 2A protein that is needed for RNA2 accumulation and colocalizes with some of the RNA1-encoded proteins (12).…”
Section: Discussionmentioning
confidence: 99%
“…Various ER-derived structures, including spherules (Brome mosaic bromovirus) and membranous vesicles or rosettes (picornavirus superfamily), are found in infected cells (3,4,6,32,33,41). Viral nonstructural proteins and RNA synthesis localize to these modified ER structures, suggesting that they are the sites of viral replication.…”
mentioning
confidence: 99%